Development of the AnimalSeek method to evaluate the localisation ability of children under five - McCartney, Damon Andrew (2013)
This thesis describes the development of a novel game-like method, the AnimalSeek method, which can be used, along with motion tracking technology, to measure localisation ability of a child under five years of age. For the game-like task to be successful, a high number of responses (in particular correct head turn responses) was required. Previous studies, although not all looking at localisation ability, have used many different techniques to obtain the maximum number of responses from a child. The children were engaged inside a custom-built environment inside an anechoic chamber. Three large video screens onto which backgrounds and animated characters were projected and manipulated and used to engage the child in the game-like task. Behind the video screens were loudspeakers from which the auditory stimulus where presented. A correct response to the auditory stimulus i.e. a head, hand or eye movement towards the target speaker was rewarded with a animated character presented on the screens (incorrect responses were presented with a static character). The location of the reward in relation to the auditory stimulus was a point of interest and was investigated to see how it affected the number of responses. The method shows it was possible to engage the child with the visual environment and obtain responses, however, the results showed generally fewer head turn responses than expected, especially in the younger age groups. Motion tracking technology was used to measure the localisation ability of the children, as well as measuring the responses, the motion tracking data was used and programs developed which could automatically classify the responses the children made to the sounds. The thesis has shown that it is possible to devise a new method which can be used to engage the child in the task and extract and classify their responses to auditory stimuli in order to measure their localisation ability.